Sobre combates e defesas do corpo na modernidade líquida: a radicalização dos conselhos privatizados para o indivíduo saudável - Gomes, Ivan Marcelo (2014)
This text is part of a broader study addressing the development of discourses on healthy living in modernity. Based on Zygmunt Bauman's sociology, we aim at interpreting how concerns about health and body care are widespread in contemporary society. The central argument in this paper is that there is, in these demands, an intersection of scientific pretensions and a crusade in the name of a "correct" lifestyle